PREDIKSI PENGGANTIAN MINYAK PELUMAS MOTOR DIESEL GENERATOR SET BERDASARKAN LAJU PERUBAHAN VISKOSITAS DAN TOTAL BASE NUMBER DENGAN PENDEKATAN LINIERITAS - Mohammad Galbi; Ishak A (Bina Teknika, 2016)
Diesel engine as the prime mover or as an auxiliary motor is still very dominant use on the ship. Diesel engines can operate with the same four-stroke cycle gasoline engine with: intake, compression, combustion and exhaust. One advantage of the diesel engine is the fuel consumption is better than gasoline engines due to lower pumping loss and high compression ratio. Conversely, there are drawbacks, such as vibration and noise during operation and large this state will increase along with the deterioration of the quality of lubricants. To detect thecondition of lubricants can be done by measuring the viscosity and total base number (TBN) .. Nevertheless, every machine has different characteristics from each other, so as to know the condition of engine lubricant is casuistry anyway. In this case, replacement of engine lubricant boat with linearity approach is on a machine that has a high reliability aimed at determining the condition of engine lubricant according to the hours of operation.